Liability gap, personhood theories and effective AI legal framework in the GCC countries: shariah as the thread that binds - Abdul Ghani Azmi, Ida Madieha; Daud, Mahyuddin (Palgrave Macmillan, 2025)
The rapid transformation of the GCC countries is now being supported with ambitious national plans to deploy AI and emerging technologies. The Saudi’s Vision 2030 that has been cited as a model for other GCC countries, for example, outlines several key initiatives including the setting up of institutions to oversee the development and governance of AI in the country.